EVALUASI KUALITAS LINGKUNGAN ESTUARI DI MUARA DAERAH ALIRAN SUNGAI (DAS) BEDADUNG KABUPATEN JEMBER - , Nasobi Niki Suma ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Estuaries, coastal area, and watershed perform as asystems that influence each another. The lack of awareness and preservation on the importance of estuarial ecosystem is experienced by local community . This causes estuarial ecosystem changes into landfill pollutant, as what occurs in Bedadung Estuarial Ecosystem in Jember. The aims of this research are: (1) to assess the enviromental quality of estuary in Bedadung watershed, (2) to analyse the distribution of pollutant source in Bedadung watershed, (3) to propose an integrated estuarial management in Jember. The method used in this research is scoring analysis, spatial analysis using ArcGIS 10.2, and SWOT analysis. The researchâs location consists of inside area (estuary) and outside area (river system in a watershed). Sampling method used in inside area is stratified random sampling. Whilst the sampling method using in outside area and communityâs activity is purposive sampling. The result of this research showed that enviromental quality of Bedadung estuary is at moderate level, which is the state where the quality of estuarial waters occuring stress. Most pollutant sources areincluded as non-point sources. Projection of the biggest pollutant sources occurs in segment 2 (10.69 km â 30.8 km from the upper stream), the values of domestic sewages are 30.843.565,80 m 3 /year and paddy field irrigation sewages are 313,14 m 3 /year. Integrated estuarial management among communities, government, agencies, and related department is needed to preserve the sustainabilityof Bedadung estuary.